Combatting Illegal Fishing as a Top Priority in Developing Sustainable Blue Economy Management - Alvarenza Willy Ara (Journal of World Trade Studies, 2023)
This article addresses a critical issue in the context of the blue economy, which is illegal fishing, and makes it the primary focus in efforts to maintain the sustainability of marine resources. In the era of the rapidly developing blue economy, it is important to understand the negative impacts caused by illegal fishing practices and how this damages marine ecosystems and the potential of the blue economy. The author explores the impacts caused by illegal fishing. The author identifies marine resource management strategies that have been implemented to combat illegal fishing, as well as the role of increasingly sophisticated technology in monitoring and controlling this illegal activity, and the importance of international collaboration in global efforts to combat illegal fishing and how regulation and public policy play an important role in protecting the blue economy. Apart from that, joint efforts are also needed, both in terms of regulations and public awareness. The research method used in this research is library research using a descriptive approach to gain further understanding. This research has great benefits in maintaining the sustainability of marine resources, strengthening the empowerment of coastal communities, and supporting the growth of the blue economy by overcoming illegal fishing, which threatens the sustainability of the ecosystem and economy.